The influence of institutional ownership, leverage and profitability on tax avoidance: Empirical study on mining sector companies - Agusta, Marcho; Sormin, Feber (WIM Solusi Prima, 2025)
This study aims to analyze and examine the influence of institutional ownership, leverage, and profitability on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. Tax avoidance is a legal strategy used by companies to minimize tax burdens, yet it often raises concerns as it may reduce the company’s tax contributions to the state. The research employs a quantitative approach with secondary data collected from annual financial reports. The sample was selected using a purposive sampling technique, resulting in 23 companies from a population of 63, with a total of 92 observations. Data were analyzed using mmultiple linear regression with the assistance of SPSS software. The result indicate that leverage has a positive and significant effect on tax avoidance, suggesting that companies with higher debt ratios tend to engage more in tax avoidance. In contrast, institutional ownership and profitability have a negative effect on tax avoidance, implying that companies with higher institutional ownership and profitability levels re less likely to avoid taxes. These findings provide insights for management, investors, and tax authorities regrading corporate behavior in managing tax obligations, and emphasize the importance of enhanced oversight of tax avoidance practices.